2012
DOI: 10.1155/2012/315203
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Atypical Antipsychotics on Fetal Growth: Is the Placenta Involved?

Abstract: There is currently considerable uncertainty regarding prescribing practices for pregnant women with severe and persistent psychiatric disorders. The physician and the mother have to balance the risks of untreated psychiatric illness against the potential fetal toxicity associated with pharmacological exposure. This is especially true for women taking atypical antipsychotics. Although these drugs have limited evidence for teratological risk, there are reports of altered fetal growth, both increased and decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 109 publications
1
11
0
Order By: Relevance
“…Although it is known that all psychotropic medications cross the placenta [34], there is uncertainty regarding the teratogenic effects of antipsychotics on pregnancy [37]. One of the reasons for this is the previous lack of high-quality evidence.…”
Section: The Effects Of Antipsychotic Medications On Fetal Morphologymentioning
confidence: 99%
See 2 more Smart Citations
“…Although it is known that all psychotropic medications cross the placenta [34], there is uncertainty regarding the teratogenic effects of antipsychotics on pregnancy [37]. One of the reasons for this is the previous lack of high-quality evidence.…”
Section: The Effects Of Antipsychotic Medications On Fetal Morphologymentioning
confidence: 99%
“…The exposure of these medications in utero has been reported to result in an increased incidence of both low and high birth weight compared to the general population. However, this association remains unclear due to conflicting results in a number of observational studies [37]. Newham et al [40] prospectively examined newborns exposed to either classes of antipsychotics and observed that newborns exposed to atypical antipsychotics had a significantly higher risk of being large for gestational age (LGA) and presented a higher birth weight mean than those exposed to typical antipsychotics.…”
Section: The Effects Of Antipsychotic Medications On Neonatal Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…The only report is one review article (Raha et al . ). Hence, this laboratory is a pioneer in reporting placental and foetal toxicity and their correlation when AAPDs like RIS was administered to pregnant rats.…”
Section: Discussionmentioning
confidence: 97%
“…Maternal exposure to drugs or chemicals may induce placental injuries and subsequently lead to placental dystrophy, reproductive toxicity, impaired foetal growth and development as well as congenital malformations depending upon the drug doses and exposure period (Raha et al . ; Furukawa et al . ,b).…”
Section: Discussionmentioning
confidence: 99%